Pulse Parameters and Peak Currents of Return Strokes Observed by the Ningxia FALMA in the Chinese Inland Areas - Dongdong Shi; Panliang Gao; Ting Wu; Daohong Wang; Wei Jiang (Remote Sensing, 2022)
We have studied the pulse parameters and peak currents of 17,225 return stroke (RS) events in the cloud-to-ground lightning flashes observed in Chinese inland areas by a multistation mapping system called Ningxia Fast Antenna Lightning Mapping Array. There are a total of 685 positive and 16,540 negative RS events, respectively, producing 8280 and 195,860 pulses at multi stations. It is found that on average, the positive RS pulse appears to have a longer rise time, wider half-peak width, shorter fall time and longer zero-crossing time than the negative RS pulse. The RS peak currents are estimated through time-matching with a modest number of RS from the calibrated lightning location system. The statistical results show that the arithmetic means of positive and negative RS peak currents are 31.5 and 22.8 kA, respectively. Compared to previously reported studies, both the RS pulse parameters and peak currents are significantly different. Particularly, we note that in our dataset, the percentage of positive RSs with peak currents below 10 kA is up to 27%, a significant number which should be taken into account in such types of statistical studies. Additionally, we have further used the data from Gifu, Japan, and Ningxia, China, to verify how distance ranges and observation regions affect the RS characteristics. The results have provided distinct evidence that the distance ranges and observation regions should be at least two of the factors attributing to the statistical disparities among different studies.